The Present in Flemish Secondary History Education Through the Lens of Written History Exams - Van Nieuwenhuyse, Karel; Wils, Kaat; Clarebout, Geraldine; Verschaffel, Lieven (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
The present plays an important part in history education, in particular in efforts to make the study of the past relevant for today. This contribution examines how the relationship between past and present is dealt with in current Flemish secondary history education by analyzing 190 written history exams for the 11th and 12th grade. Ten percent of the questions address the present in an autonomous way and 8% relate past and present to each other. A more fine-grained analysis of the present-related questions reveals a variety of ways to integrate the present in history education, including the study of recent interpretations of the past.